EVALUASI PROGRAM LATIHAN FISIK SEPAKBOLAMENGGUNAKAN METODE CIPP PADA PENDIDIKAN SEPAK BOLA KABUPATEN NGAWI TAHUN AJARAN 2015/2016 - Kustiawan, Andri Arif (Jurnal Phederal Penjas, 2015)
This study aims to determine: (1) The form and content of programs of physical exercise in each Education Football entire Ngawi; (2) The physical exercise program in each Education Football whole Ngawi 2015. .Penelitian use descriptive method with survey techniques. Subjects of the research is that there are entire populations throughout the coach of each PSB se Ngawi totaling 14 PSB. Data collection technique used is the instrument which contains a set of questionnaires, to reveal the extent of the coach planned physical exercise as well as the kind of action trainers in the training process. Data analysis techniques used in this study quantitatively with the help of descriptive statistical analysis. Based on the results of this study indicate that the results of the planning exercise program from the coaches menyatakan43,45% is appropriate, 44.075% undecided, and 12.475% is not appropriate. While the results of the implementation of a training field for the attainment of peak condition coach players on measures before the implementation of activities amounted to 61.4%, the creation of conditions in the training of 76.2%, the difference in the players specialization of 71.4%, about the use of methods 76.4% practice, the interaction between the coach and the players in the training process 73.8%, regarding the use of the equipment in the exercise of 64.3%, regarding the provision of guidance in the exercise of 77.5%, regarding the evaluation of training results 69.4%. The conclusion of this study about the plan form of physical exercise program from the coaches to the achievement of peak condition players who have been determined through the stages of periodization of the execution of a physical exercise program, Education Football se Ngawi 2015/2016 school year is already carrying out a physical exercise program good.